Exploring it issues and application in the context of Malaysia - Hussin, Husnayati (s.n, 2012)
IT outsourcing (ITO), a means of of acquiring IT resources externally, has become a popular trend worldwide not only among companies in developed countries but also in developing ones. While IT outsourcing is widely adopted by large organization, small and medium-sized enterprises (SMEs) have also begun to realize the potentials of using IT outsourcing services. The uptake of IT outsourcing among SMEs in Malaysia is noticeable but not much research has been conducted to examine the issue. This study was undertaken to gauge the level of IT outsourcing utilization among Malaysia SMEs and to understand why some are not using it. The objective of the study was to examine the current scenario of IT outsourcing practices among Malaysia SMEs. Based on a survey conducted, a descriptive analysis was performed on the data. The findings revealed that about 40% of the sample has adopted ITO and cited gaining access to technical expertise as the main motivation. Those that did not engage in acquiring ITO services perceived that they did not need such services. Overall, the results imply that there is positive indication among the SMEs toward ITO adoption, which adds credit to the overall ITO expansion in Malaysia